2004
DOI: 10.1542/peds.2004-0961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Home Visits by Paraprofessionals and by Nurses: Age 4 Follow-Up Results of a Randomized Trial

Abstract: Paraprofessional-visited mothers began to experience benefits from the program 2 years after the program ended at child age 2 years, but their first-born children were not statistically distinguishable from their control group counterparts. Nurse-visited mothers and children continued to benefit from the program 2 years after it ended. The impact of the nurse-delivered program on children was concentrated on children born to mothers with low levels of psychologic resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
379
1
19

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 410 publications
(405 citation statements)
references
References 39 publications
6
379
1
19
Order By: Relevance
“…Social support is a concept that is perhaps less familiar to physicians. However, randomized trials of the provision of social support to new parents have shown lasting positive impacts for children, at least when done by nurses [49][50][51]. At this point, it seems reasonable to recommend an opportunistic approach of awareness, screening as much as possible, and intervening where leverage is available, based on physician, patient, and local resources.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is a concept that is perhaps less familiar to physicians. However, randomized trials of the provision of social support to new parents have shown lasting positive impacts for children, at least when done by nurses [49][50][51]. At this point, it seems reasonable to recommend an opportunistic approach of awareness, screening as much as possible, and intervening where leverage is available, based on physician, patient, and local resources.…”
Section: Discussionmentioning
confidence: 99%
“…• Increase parents' sensitivity to their children, reduce negativity towards children, improve parents' emotional abilities, expressiveness, responsiveness and sensitivity in interactions and nurturing behaviors, help parents be less intrusive and better able to support children's independence (Brooks-Gunn, Berlin, and Fuligni 2000;Cooper et al 2002;Heinicke et al 2001;Olds et al 2004). …”
Section: Evidence That Parenting Programs Work When Implemented Wellmentioning
confidence: 99%
“…62,63 Similarly, in the other 2 trials (Memphis and Denver), the NFP program did not reduce the children's DBD symptoms during childhood. 64,65,71 …”
Section: Preventive Experiments For Dbdsmentioning
confidence: 99%